A Comparative Analysis of Evacuation Safety on Stairs and Ramp for High School Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study, assuming evacuation training in high school buildings, compared and analyzed the evacuation safety of two escape routes, stairs and ramps. In the gender-based evacuation experiment, male students' RSET(Required Safe Egress Time) was shorter in all scenarios of stairs and ramps, and both male and female students' RSET on ramps was shorter than stairs. In the grade-by-year experiment, third-grade students who are familiar with school facilities had shorter RSET on both stairs and ramps than first-year students. The students who participated in the experiment reported that it was difficult to evacuate due to the steep stairs and narrow field of view and that it was easy to evacuate the ramps because the field of view was wide and stable by contrast. In conclusion, students both by gender and grade were analyzed to have higher escape safety on ramps than stairs. Therefore, it was shown that there is the need to strengthen the installation of ramps in public buildings to minimize human damage and ensure evacuation safety in case of fire